Genome-wide association study identifies multiple new loci associated with Ewing sarcoma susceptibility - Machiela, Mitchell J.; Kulozik, Andreas (Nature Communications, 2018)
Ewing sarcoma (EWS) is a rare pediatric bone cancer typically involving the EWSR1-FLI1 fusion. Here the authors perform a genome-wide association study and report three new EWS risk loci that reside near GGAA repeat sequences, and identify candidate genes (RREB1 and KIZ) from eQTL analysis.
Gesehen am 07.08.2019